2019
DOI: 10.1002/pon.5051
|View full text |Cite
|
Sign up to set email alerts
|

Women's perceptions of personalized risk‐based breast cancer screening and prevention: An international focus group study

Abstract: Objective Increased knowledge of breast cancer risk factors enables a shift from one‐size‐fits‐all breast cancer screening to a risk‐based approach, tailoring screening policy to a woman's individual risk. New opportunities for prevention will arise. However, before this novel screening and prevention program is introduced, its acceptability from a woman's perspective needs to be explored. Methods Women eligible for breast cancer screening in the Netherlands, United Kingdom, and Sweden were invited to take par… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
117
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 42 publications
(125 citation statements)
references
References 21 publications
(26 reference statements)
8
117
0
Order By: Relevance
“…We found that 10% of women were unsure about whether they would want to know their breast cancer risk. Our previous focus group study indicated several underlying factors affecting women's indecision, such as perceived emotional burden and lack of self-efficacy [8]. It additionally showed that women who were unsure about participation in the new risk-based screening programme tended to perceive a greater need for information [8].…”
Section: Discussionmentioning
confidence: 98%
See 4 more Smart Citations
“…We found that 10% of women were unsure about whether they would want to know their breast cancer risk. Our previous focus group study indicated several underlying factors affecting women's indecision, such as perceived emotional burden and lack of self-efficacy [8]. It additionally showed that women who were unsure about participation in the new risk-based screening programme tended to perceive a greater need for information [8].…”
Section: Discussionmentioning
confidence: 98%
“…A first qualitative exploration of the acceptability of risk-based breast cancer screening and prevention among a small group of women eligible for screening in the Netherlands, the United Kingdom, and Sweden confirmed the controversial nature of reduced screening intensity [8]. Women also expressed reluctance about participating in preventative practices to decrease their breast cancer risk.…”
Section: Introductionmentioning
confidence: 95%
See 3 more Smart Citations